2014
DOI: 10.1017/s0047279414000841
|View full text |Cite
|
Sign up to set email alerts
|

Creaming and Parking in Quasi-Marketised Welfare-to-Work Schemes: Designed Out Of or Designed In to the UK Work Programme?

Abstract: ‘Creaming’ and ‘parking’ are endemic concerns within quasi-marketised welfare-to-work (WTW) systems internationally, and the UK's flagship Work Programme for the long-term unemployed is something of an international pioneer of WTW delivery, based on outsourcing, payment by results and provider flexibility. In the Work Programme design, providers’ incentives to ‘cream’ and ‘park’ differently positioned claimants are intended to be mitigated through the existence of nine payment groups (based on claimants' prior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
96
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(99 citation statements)
references
References 10 publications
0
96
0
3
Order By: Relevance
“…Moreover, new governance models are based on what is widely referred to as public sector 'managerialism', which is a third facet of disorganisation. These models comprise quasi-commercial 'public-private partnerships', 'performance-based contracting', and meticulous process control mechanisms (Clarke et al, 2000;Harlow et al, 2013;Lawrence and Lyons, 2013;Carter and Withworth, 2015). In this context, collaboration between nonstatutory instances and the state has become instrumental and troublesome in many places (Bode and Brandsen, 2014).…”
Section: Tragic Moments: Paradoxical (Re-)privatisation and Disorganimentioning
confidence: 99%
“…Moreover, new governance models are based on what is widely referred to as public sector 'managerialism', which is a third facet of disorganisation. These models comprise quasi-commercial 'public-private partnerships', 'performance-based contracting', and meticulous process control mechanisms (Clarke et al, 2000;Harlow et al, 2013;Lawrence and Lyons, 2013;Carter and Withworth, 2015). In this context, collaboration between nonstatutory instances and the state has become instrumental and troublesome in many places (Bode and Brandsen, 2014).…”
Section: Tragic Moments: Paradoxical (Re-)privatisation and Disorganimentioning
confidence: 99%
“…Należy również podkreślić czas, na jaki kontrakt jest zawierany, a w Polsce wynosi on jeden rok, co może również zniechęcać określone instytucje do ubiegania się o jego realizację. W Holandii kontrakty mogą być realizowane do dwóch lat (de Koning 2004), a Wielkiej Brytanii do siedmiu (Carter 2015). Wydłużenie okresu ich realizacji ma zachęcić wykonawców do inwestowania w kapitał ludzki, rzeczowy, organizacyjny w celu zapewnienia wysokiej jakości usług aktywizacyjnych.…”
Section: Szanse I Zagrożenia Jakie Tworzy Kontraktacja Dla Rynku Pracyunclassified
“…Dlatego w walce z efektem parkowania można zastosować zróżnicowane stawki wynagrodzeń dla realizatorów kontraktów, uwzględniając stopień oddalenia od rynku pracy bezrobotnych. I tak w Wielkiej Brytanii o wiele wyższe opłaty stosowano za aktywizację byłych więźniów w porównaniu do osób młodych (Carter 2015).…”
Section: Szanse I Zagrożenia Jakie Tworzy Kontraktacja Dla Rynku Pracyunclassified
“…Research suggests that performance management systems and quasi-markets encourage these practices (Bredgaard and Larsen, 2008;Crisp et al, 2011;Koning and Heinrich, 2010), although the causes of this 'risk selection' should not be over-simplified (van Berkel, 2014). There is some qualitative evidence of creaming and parking in the WP, but the evidence is hard to determine (Newton et al, 2012;Carter and Whitworth, 2015). Recent quantitative research has suggested that creaming and parking have been designed into the WP as a result of insufficient differential payments to encourage support for those furthest from the labour market (Carter and Whitworth, 2015).…”
Section: Activation Of the Long-term Unemployed In The Ukmentioning
confidence: 99%
“…There is some qualitative evidence of creaming and parking in the WP, but the evidence is hard to determine (Newton et al, 2012;Carter and Whitworth, 2015). Recent quantitative research has suggested that creaming and parking have been designed into the WP as a result of insufficient differential payments to encourage support for those furthest from the labour market (Carter and Whitworth, 2015).…”
Section: Activation Of the Long-term Unemployed In The Ukmentioning
confidence: 99%